Antioxidant, antimicrobial, enzyme inhibition, and cytotoxicity guided investigation of Sideroxylon mascatense (A.DC.) T.D. Penn. leaves extracts. Issue 16 (29th July 2022) - Ali, Joham Sarfraz; Riaz, Naheed; Mannan, Abdul; Latif, Muhammad; Zia, Muhammad
Abstract: The present study demonstrates the pharmacological tendency of Sideroxylon mascatense leaves extracts, fractions and sub-fractions using thin layer chromatography, column chromatography, and phytochemical (phenolics, flavonoids) and biological assays (free radical scavenging, antioxidative, antimicrobial, enzyme inhibition). The results disclosed that fractionation practice accumulated the active phytochemicals in few fractions and finally leads to the isolation of active compounds. The structural elucidation was carried out using spectroscopic 1D ( 1 H, 13 C) 2D NMR and spectrometric techniques. The n -hexane fraction led to isolation of lupeol. From the CHCl3 and EtOAc fractions, two compounds were isolated, hentriacontanol, and lupeol, respectively. The isolated compounds were also characterized for biological activities. This study concludes that bioactivity guided isolation can be performed for isolation of active constituents from S. mascatense which can be further explored for drug development. Graphical Abstract: UF0001